Perceived Organizational Support and Psychological Empowerment: A Multi-Sample Study. Issue 7 (July 2020) - Caesens, Gaëtane; Bouchat, Pierre; Stinglhamber, Florence
Abstract : N/A: This research examined the mediating role of employees' psychological empowerment in the relationship between perceived organizational support and employee psychological well-being. Our hypotheses were tested using three different sets of cross-sectional data ( N  = 237, N  = 334, and N  = 182). Results indicated across the three samples that psychological empowerment mediates the positive relationship between perceived organizational support and employee psychological well-being. Implications for organizational support and psychological empowerment literatures are discussed.